Surface-confined heterometallic molecular dyads: merging the optical and electronic properties of Fe, Ru, and Os terpyridyl complexes - Gupta, Tarkeshwar; Jeyachandran, Yekkoni Lakshmanan; Zharnikov, Michael (Advanced functional materials, 2013)
Molecular assemblies of surface-confined heterometallic molecular dyads (SURHMDs) composed of optically rich and redox-active Fe(pytpy)2·2PF6 (Fe-PT), Ru(pytpy)2·2PF6 (Ru-PT) and Os(pytpy)2·2PF6 (Os-PT) pytpy = 4′-(4-pyridyl)-2,2′:6′,2″-terpyridyl] complexes are fabricated via bottom-up approach on SiOx based solid supports. Pairing of the two different metal-organic complexes at a single platform results in significant enlargement of the optical window (λ = 400-800 nm), which can be of interest for potential applications. The use of the Cu-based linker ensures intramolecular electronic communication between these complexes. In addition, SURHMDs are electrochemically stable under large numbers of read-write cycles (103) and exhibit multiple redox states at relatively low potentials (<1.2 V). Moreover, an electrochemical input at controlled potentials creates a mixed-valence multicomponent system.